2020
DOI: 10.1111/idj.12533
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and knowledge of oral cancer amongst adult dental patients attending regional university clinics in New South Wales, Australia: a questionnaire-based study

Abstract: Background Greater awareness and knowledge of oral cancer has been shown to increase patient presentation for opportunistic screening. This study aimed to identify the level of awareness and knowledge of oral cancer amongst adult patients in regional New South Wales. Methods A total of 444 adult dental patients participated in a self‐administered questionnaire at one of five regional university dental clinics between 23rd May and 25th July. Data analyses were performed using the chi‐square test and binary logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(53 citation statements)
references
References 36 publications
3
46
2
2
Order By: Relevance
“…Overall, the outcomes of this study could be applied to identify at higher risk target groups and improve their awareness and knowledge of oral cancer. This was prompted by the literatures reporting a causality between areca nut consumption and oropharyngeal cancer (Chen et al., 2017; Chuang et al., 2017; Jeng et al., 2001; Wu et al., 2018), and the moderate awareness and limited knowledge relating to oral cancer in the general public (Zachar, Huang, & Yates, 2020). Furthermore, areca nut consumption is addictive (Winstock, 2002) and prone to social influence (Hussain et al., 2017; Tsai et al., 2002; Wang et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the outcomes of this study could be applied to identify at higher risk target groups and improve their awareness and knowledge of oral cancer. This was prompted by the literatures reporting a causality between areca nut consumption and oropharyngeal cancer (Chen et al., 2017; Chuang et al., 2017; Jeng et al., 2001; Wu et al., 2018), and the moderate awareness and limited knowledge relating to oral cancer in the general public (Zachar, Huang, & Yates, 2020). Furthermore, areca nut consumption is addictive (Winstock, 2002) and prone to social influence (Hussain et al., 2017; Tsai et al., 2002; Wang et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…6 Zachar ve ark. 29 yetişkin hastalarda ağız kanseri farkındalığını araştırdıkları çalışmada ağız kanserinin etiyolojik faktörleri için katılımcıların %94,4'ü sigara, %57,1'i alkol yanıtını verdiklerini bildirdi. Çalışmamızda ağız kanserine yönelik etiyolojik faktörleri sorguladığımızda ise katılımcıların %18 (n=90)'ı oral hijyen yetersizliği, %9,8 (n=49)'i sigara, %0,2 (n=1)'i alkol, %48,4 (n=242)'ü ise 'bilmiyorum' cevabını verdi.…”
Section: Gereç Ve Yöntemunclassified
“…West et‐al.‐ (2006) reported that most patients fail to recognize the early signs and symptoms of OC and consequently, many cancers remain undetected in the early stages of disease 18 . The literature to date has identified that lack of awareness and knowledge of OC risk factors and early clinical signs and symptoms of disease may hinder early OC diagnosis 19–21 . Conversely, patients with a sound awareness and knowledge of the risk factors, and clinical signs and symptoms of OC, are more likely to present to GDPs for opportunistic screenings that facilitate early detection 22 …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies conducted, both in Australia and abroad, have reported that roughly 45–70% of the general population are aware of the existence of OC 11,17,23–25 . Alarmingly, the majority of dental participants in Australian studies were unaware of having ever received an OC screening by their GDP 21,25,26 . Early diagnosis of OC can be facilitated by opportunistic screening for OC signs and symptoms among patients attending primary healthcare settings for routine dental or medical care 21,22,25–27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation